2018
DOI: 10.1111/jipb.12609
|View full text |Cite
|
Sign up to set email alerts
|

Nicotiana attenuata's capacity to interact with arbuscular mycorrhiza alters its competitive ability and elicits major changes in the leaf transcriptome

Abstract: To study the local and systemic effects of arbuscular mycorrhizal fungal (AMF) colonization, Nicotiana attenuata plants impaired in their interactions with AMF due to silencing of a calcium- and calmodulin dependent protein kinase (inverted repreat (ir)CCaMK) were grown competitively in pairs with empty vector (EV) plants, with and without two different types of inoculum. When inoculated, EV plants strongly outperformed irCCaMK plants. Foliar transcript profiling revealed that AMF colonization significantly ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 88 publications
(132 reference statements)
2
38
0
Order By: Relevance
“…By choosing the OS-elicited JA-mediated defences of the N. attenuata system, we were able to build on the large knowledge base of prior information available in this system (Groten et al, 2015;Wang, Wilde, et al, 2018) and germane to this discussion, the ability to exclude interplants defence signalling mediated by plant volatiles (Paschold et al, 2006). In the N. attenuata system, it is well established that plant size, growth stage, and tissues influence both constitutive and inducible JA-mediated defences (Baldwin, Schmelz, & Ohnmeiss, 1994;Stitz, Gase, Baldwin, & Gaquerel, 2011;Stitz, Hartl, Baldwin, & Gaquerel, 2014;Stork, Diezel, Halitschke, Galis, & Baldwin, 2009) and that AMF associations influence plant size (Riedel et al, 2008;Wang, Wilde, et al, 2018); hence, it was critical to compare W + OS-elicited response in the same tissues from plants that were of the same size and developmental stage. To this end, we designed the mesocosms to contain four different groups (Figure 3a) that included controls in which plants of a mesocosm had shared a CMN association up until 7 days before the W + OS elicitation of the "donors," when the AMF network linking the four plants of each mesocosm was removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By choosing the OS-elicited JA-mediated defences of the N. attenuata system, we were able to build on the large knowledge base of prior information available in this system (Groten et al, 2015;Wang, Wilde, et al, 2018) and germane to this discussion, the ability to exclude interplants defence signalling mediated by plant volatiles (Paschold et al, 2006). In the N. attenuata system, it is well established that plant size, growth stage, and tissues influence both constitutive and inducible JA-mediated defences (Baldwin, Schmelz, & Ohnmeiss, 1994;Stitz, Gase, Baldwin, & Gaquerel, 2011;Stitz, Hartl, Baldwin, & Gaquerel, 2014;Stork, Diezel, Halitschke, Galis, & Baldwin, 2009) and that AMF associations influence plant size (Riedel et al, 2008;Wang, Wilde, et al, 2018); hence, it was critical to compare W + OS-elicited response in the same tissues from plants that were of the same size and developmental stage. To this end, we designed the mesocosms to contain four different groups (Figure 3a) that included controls in which plants of a mesocosm had shared a CMN association up until 7 days before the W + OS elicitation of the "donors," when the AMF network linking the four plants of each mesocosm was removed.…”
Section: Discussionmentioning
confidence: 99%
“…Excavated roots from field-grown plants exhibited the characteristic structures of AMF symbiosis: arbuscules. By sequencing, the AMF species were identified as Rhizophagus irregularis and F. mosseae (Groten, Nawaz, Nguyen, Santhanam, & Baldwin, 2015;Wang, Wilde, Baldwin, & Groten, 2018). Extensive research with the N. attenuata model system has demonstrated that VOCs signals from herbivores-attacked neighbours do not prime neighbouring "receiver" plants, which show no differences in JAs levels or any other defensive traits elicited by treating puncture wounds with oral secretions (OS) from Manduca sexta larvae (Paschold, Halitschke, & Baldwin, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi colonization has been found to profoundly alter gene expression in roots of several plants species (Guimil et al, 2005;Fiorilli et al, 2009;Guether et al, 2009;Hogekamp & Küster, 2013;Groten et al, 2015), whereas a number of large-scale gene expression studies have explored the systemic effects that AMF root colonization has in plant aerial tissues (Guimil et al, 2005;Cervantes-Gamez et al, 2016;Adolfsson et al, 2017;Wang et al, 2018a). Changes in root and leaf metabolite levels in response to AMF colonization, have been also reported, particularly affecting amino acid (aa), carbohydrate and organic acid contents (Schweiger et al, 2014;Rivero et al, 2015;Schweiger & Müller, 2015;French, 2017;Bedini et al, 2018;Wang et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Several of the above effects are finely regulated by phytohormones, via a limitedly understood and highly context dependent interaction (Ruiz-Lozano et al, 2012;Gutjahr 2014;Selosse et al, 2014;Pozo et al, 2015). AMF colonization has been found to profoundly alter gene expression in roots of several plants species (Guimil et al, 2005;Fiorilli et al, 2009;Guether et al, 2009;Hogekamp and Kuester, 2013;Groten et al, 2015), whereas a number of large-scale gene expression studies have explored the systemic effects that AMF root colonization has in plant aerial tissues (Guimil et al, 2005;Cervantes-Gamez et al 2016;Adolfsson et al, 2017;Wang et al, 2018). Changes in root and leaf metabolite levels in response to AMF colonization, have been also reported, particularly affecting amino acid (aa), carbohydrate and organic acid contents (Fester et al 2011;Schweiger et al 2014;Rivero et al, 2015;Schweiger and Müller, 2015;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%